2014
DOI: 10.1007/s13361-014-1046-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Loeb-Eiber Mass Filter at 1 Torr

Abstract: Abstract. The Loeb-Eiber mass filter is best operated at relatively high pressures-such as 1 Torr-where collisional dampening of ions up to the mass filter thermalizes the ions' kinetic energy, which is a requirement for effective filtering. The inter-electrode gaps of~8 μm require rf amplitudes on the order of 0-5 V p-p at approximately 50 MHz to achieve mass filtering up to m/z 40. Mass filtering between the 25-μm diameter wires, therefore, takes place on time frames less than the collision frequency at~1 To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…These conditions promote Penning ionization of He* with not only H 2 O (reaction (14)) but also N 2 and O 2 (reactions (16) and (17)), having ionization energies of 14.5 and 13.6 eV, respectively. These conditions promote Penning ionization of He* with not only H 2 O (reaction (14)) but also N 2 and O 2 (reactions (16) and (17)), having ionization energies of 14.5 and 13.6 eV, respectively.…”
Section: Improving (De)protonation Efficiency Of Corona-dartmentioning
confidence: 99%
See 2 more Smart Citations
“…These conditions promote Penning ionization of He* with not only H 2 O (reaction (14)) but also N 2 and O 2 (reactions (16) and (17)), having ionization energies of 14.5 and 13.6 eV, respectively. These conditions promote Penning ionization of He* with not only H 2 O (reaction (14)) but also N 2 and O 2 (reactions (16) and (17)), having ionization energies of 14.5 and 13.6 eV, respectively.…”
Section: Improving (De)protonation Efficiency Of Corona-dartmentioning
confidence: 99%
“…This feature allows DART to be used for the direct analysis of narcotics, 6 addictive drugs, 7 counterfeit drugs, 8 microorganisms, 9 warfare agents, 10 pesticides, 11 for quality control, 12 in organic syntheses monitoring, 13 and for the surface analysis of living organisms. Thus, DART makes direct and highly sensitive analyte measurements feasible, as compared to typical low-pressure plasma ion sources using glow discharge 16 or dielectric barrier discharge. The desorption is carried out using hot helium gas, whereas the ionization goes through an atmospheric pressure chemical ionization (APCI)-like process involving ion-molecule reactions with excited helium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many current fieldable mass spectrometry systems push boundaries of MS miniaturization, such as the MMS 100 and OEM-100 from 1 st Detect and the Griffin 400 series and Griffin 844 from FLIR, , but all of these systems require turbo pumps for operation. With the development of a discontinuous atmospheric pressure interface (DAPI), ion trapping has been performed at elevated pressures (∼1 Torr), but a turbo pump is still needed to reach lower pressures for mass analysis (<10 mTorr). , Hoffman et al have shown high-pass mass filtering for ions of low m / z (<40) at 1 Torr with a MEMS based Loeb-Eiber mass filter . The Loeb-Eiber filter shows promise as a filter for ions at 1 Torr but was only used for relatively low m / z species, and mass analysis was still performed at low pressures with a linear quadrupole.…”
mentioning
confidence: 99%
“…A discontinuous atmospheric pressure interface (DAPI) has been used to trap ions at 1 Torr with air as the background gas, but mass analysis was performed at low pressures (<10 mTorr) . A Loeb‐Eiber mass filter has been used to high‐pass filter ions of low m/z at 1 Torr of air, but mass spectra were collected with a linear quadrupole operating at 10 −5 Torr after filtering . The studies mentioned above demonstrate that ion trap based mass analysis with air buffer gas is possible, but the authors were unable to perform both trapping/filtering and mass analysis at 1 Torr.…”
mentioning
confidence: 99%